Comparison of 2-D and 3-D Analysis of Running Kinematics and Actual Versus Predicted Running Kinetics - Caitlyn Martinez; Seth Garbett; Kristen Hiromasa; Rhandi Jackson; Eric Miya; Michelle Miya; Joshua D White; Brian S Baum; Mark F Reinking (International Journal of Sports Physical Therapy)
# Background